Kohesivitas Kelompok ditinjau dari Komunikasi Interpersonal dan Komitmen Organisasi pada Organisasi Mahasiswa - Hasaniah Zulfiani; Mohammad Risqi; Jhon Mart Ramadhan (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to determine the relationship between interpersonal communication and organizational commitment with group cohesiveness in student organizations. The sample in this study consisted of 31 members of the Ahmad Dahlan University Faculty Student Executive Board. The method used is correlation. Data collection used group cohesiveness scale, interpersonal communication scale and organizational commitment scale. The analysis technique used is multiple regression analysis with SPSS 16.0 for Windows. The result showed that interpersonal communication and organizational commitment with group cohesiveness was 0.810 with p = 0.000 (<0.05). It was included thar interpersonal communication and organizational commitment have a relationship to group cohesiveness.